The relationship between environmental variation and species abundance in shrimp community (Crustacea : Decapoda : Penaeoidea) in south-eastern Brazil - Castilho, Antonio L. [UNESP]; Pie, Marcio R.; Fransozo, Adilson [UNESP]; Pinheiro, Allysson P. [UNESP]; Costa, Rogério Caetano da [UNESP] (Cambridge University Press, 2008)
The impact of shrimp fisheries in tropical regions has become comparable to the world's most intensively exploited temperate shed ecosystems. The increase in the fishing fleet in south-eastern Brazil and the decrease in landings of profitable shrimp species have contributed to the incorporation of additional species into those fisheries. The goal of the present study is to investigate the influence of environmental factors on the abundance patterns of shrimp communities on the south-eastern coast of Brazil, over a period of two years. Monthly collections were conducted in the Ubatuba and Caraguatatuba regions using a commercial shrimp fishing boat equipped with 'double-rig' nets. Each region was divided into 7 sampling stations up to 35 m deep. The relationship between the environmental factors and the abundance patterns in the shrimp communities was assessed using a canonical correlation analysis (CCorrA). The first set of variables used during the CCorrA included environmental characteristics and the second set of variables the abundance of the studied species. A total of 374,915 individuals were collected during the present study. Xiphopenaeus kroyeri showed the highest abundance (273,127), followed by Artemesia longinaris (73,422), and Pleoticus muelleri (15,262). In the first root, depth and temperature showed the highest factor loadings (0.9 and -0.7) and canonical weights (0.6 and -0.4). These environmental factors were strongly associated with the abundance of X. kroyeri (factor loading = - 0.9 and canonical weight = - 0.9). The second root demonstrated a positive relationship between abundance of P. muelleri and depth, and an inverse association with bottom temperature. The abundance patterns of X. kroyeri and P. muelleri were strongly affected by the water mass South Atlantic Central Water (cold waters =15 degrees C), which can lead to a temperature decrease in deeper areas (> 15 m). Thus, the opposite abundance trend for depth of these species might reflect bathymetric variation in temperature, a clear example of distinct behavioural differences of species of different origins, either tropical (X. kroyeri) or subantarctic (P. muelleri). The low overall association between environmental parameters and shrimp abundance patterns indicates that each studied species might have responded idiosyncratically to environmental variation, such that a general community-level response was not apparent. However, other confounding factors such as intraspecific migration patterns might have also played a role in generating the observed patterns.
Keywords: shrimp; community; variation; Brazil